(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To analyze factors related to postpartum depression (PPD) in pregnant women giving birth at the National Hospital of Obstetrics and Gynecology. Methods: This is a descriptive study on 550 pregnant women giving birth at the National Hospital of Obstetrics and Gynecology in 2020- 2021. Results: The maternal age group under 25 has a 5.84 times higher risk of PPD than the age group 25-34 (95% CI: 3.21-9.27). Unmarried women have an 11.32 times higher risk of PPD than married women (95% CI 4.64-20.1). Paying attention to the sex of the child also increases the risk of PPD by 2.73 times. Babies born before 37 weeks and weighing less than 2500g increase the risk of PPD by 4.69 times (95% CI 1.13-195) and 2.24 times (1.05-8.41), respectively. After birth, babies crying at night also increased the risk of PPD by 4.42 times (95% CI 1.6-12.3). The relationship between husband and wife is not in harmony is also a risk factor for increasing the rate of PPD. Conclusion: Non-reproductive maternal age, singleness, and farming mothers are individual factors that increase the risk of postpartum depression. Low birth weight (<2500g) or premature birth (before 37 weeks), or poor child’s condition also negatively affects the mother’s psychological well-being. The relationship between husband and wife during childbirth is also an important factor causing postpartum depression in women.